PENGEMBANGAN PENGETAHUAN SAINS ANAK USIA DINI MELALUI METODE EXPERIMEN DI PAUD WIJAYA KUSUMAH - Muginik Muginik; Titin Sumarni; Rohmalina Rohmalina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
This research raised the problem about: Early Childhood Education Teacher Education Study Program entitled "Development of Early Childhood Science Knowledge Through Experimental Methods In Paud Wijaya Kusumah". "Objectives to be achieved through this research is to know and describe: In general, the study aims to" Obtain an overview of the objective conditions of early childhood Wijaya Kusumah before applied experimental method in the lesson year 2017 / 2018.Kknow how the steps of applying experimental methods in improving child science knowledge in PAUD Wijaya Kusumah Cimahi, 2017/2018 school year. Knowing how children's learning outcomes after applied experimental methods in early childhood Wijaya Kusumah Cimahi, academic year 2017/2018. Knowing how to support and inhibit the application of experimental methods to science knowledge for early childhood. ". This research is carried out with the approach used in this study is a qualitative research approach. Sugiyono (2009: 21-22). The data source of this research is children of PAUD Wijaya Kusumah Cimahi. While a sample of 30 children and used as a refresentative sample were 2 teachers and 5 children to be the case. The research data was collected by using instrument in the form of interview guide and observation guideline. Based on the results of the discussion that has been described, the learning activities with the application of experimental methods greatly impact on increasing knowledge of children's science in POS PAUD Wijaya Kusumah. The results of observation of children's science knowledge from before and after the experiment showed optimal development.